KEEPING AND FEEDING KARAKUL SHEEP ON PASTURES IN SURKHANDARYA REGION - U. Sh. Saydaliev; Sh.B. Kurbonov (TADQIQOTLAR, 2026)
Annotasion. The article describes the feeding standards for Karakul sheep, the annual nutrient requirements of Karakul sheep, the pasture diet and their seasonal nutrition, feeding standards for Karakul sheep of different sexes and ages, as well as feeding standards for Karakul sheep supplementary feeding.